ADVANTAGES OF USING GRADED TESTS IN MOTHER TONGUE EDUCATION - Komilova Lola Nasilloyevna (Western European Studies, 2024)
This article introduces graded tests and their types that are commonly used in native language teaching, as well as examples of some types of tests for reinforcing grammar topics and understanding a new topic and text.
Keywords: native language teaching; graded tests; types of graded tests